Low luminosity Type II supernovae – IV. SN 2020cxd and SN 2021aai, at the edges of the sub-luminous supernovae class. Issue 4 (30th April 2022) - Valerin, G; Pumo, M L; Pastorello, A; Reguitti, A; Elias–Rosa, N; Gútierrez, C P; Kankare, E; Fraser, M; Mazzali, P A; Howell, D A; Kotak, R; Galbany, L; et al.
ABSTRACT: Photometric and spectroscopic data for two Low Luminosity Type IIP Supernovae (LL SNe IIP) 2020cxd and 2021aai are presented. SN 2020cxd was discovered 2 d after explosion at an absolute magnitude of Mr  = −14.02 ± 0.21 mag, subsequently settling on a plateau which lasts for ∼120 d. Through the luminosity of the late light curve tail, we infer a synthesized 56 Ni mass of (1.8 ± 0.5) × 10 −3  M⊙ . During the early evolutionary phases, optical spectra show a blue continuum ($T\, \gt $ 8000 K) with broad Balmer lines displaying a P Cygni profile, while at later phases, Ca ii, Fe ii, Sc ii, and Ba ii lines dominate the spectra. Hydrodynamical modelling of the observables yields $R\, \simeq$ 575  R ⊙ for the progenitor star, with M ej  = 7.5 M⊙ and $E\, \simeq$ 0.097 foe emitted during the explosion. This low-energy event originating from a low-mass progenitor star is compatible with both the explosion of a red supergiant (RSG) star and with an Electron Capture Supernova arising from a super asymptotic giant branch star. SN 2021aai reaches a maximum luminosity of Mr  = −16.57 ± 0.23 mag (correcting for AV  = 1.92 mag), at the end of its remarkably long plateau (∼140 d). The estimated 56 Ni mass is (1.4 ± 0.5) × 10 −2  M⊙ . The expansion velocities are compatible with those of other LL SNe IIP (few 10 3  km s −1 ). The physical parameters obtained through hydrodynamical modelling are $R\, \simeq$ 575 R⊙, M ej = 15.5 M⊙, and E = 0.4 foe. SN 2021aai is therefore interpreted as the explosion of an RSG, with properties that bridge the class of LL SNe IIP with standard SN IIP events.